Advances in business and management forecasting. Vol. 6 - Lawrence, Kenneth D.; Klimberg, Ronald K. (Advances in business and management forecasting., 2009)
The objective of this research annual is to present state-of-the-art studies in the application of forecasting methodologies to such areas as sales, marketing, and strategic decision making. (An accurate, robust forecast is critical to effective decision making.) The focus of the research annual is applications- and practitioner-oriented. The topics will normally include sales and marketing, forecasting, new product forecasting, judgmentally based forecasting, the application of surveys to forecasting, forecasting for strategic business decisions, improvements in forecasting accuracy, and sales response models. It is the direction of the editorial board to stimulate the interest of the practitioners of forecasting to methods and techniques that are relevant.